Gender in Neelam Karki Niharika’s Story ’Second Marriage’ - Joshi, Homnath (Academia Research Journal, 2023)
The presented research article is based on the gender analysis of the second marriage story collected in Neelam Karki Niharika’s Havan Katha Sangraha (2062). In this article, the story of the second marriage is presented as an analytical material and the topic of what is the state of gender in the story is presented as a major problem. In this article, the theoretical framework of www patriarchy, representation and body politics is presented and the story is interpreted and analyzed on the basis of textual analysis method, and the social exploitation, physical and mental pressure and control of women due to patriarchy in the story, as well as how women are active for their rights and self-esteem are presented as a conclusion. This article is based on qualitative method.